Trends and patterns of mortality arising from fungal infections in Brazil in a period of 11 years - Damasceno, Lisandra Serra; Pessoa, Gabriel Melo Ferraz; Timbó, Sabrina Soares; Lima, Nícolas Breno Gomes de; Barbosa Neto, José de Paula; Coelho, Rafael Costa; Vale, Lucas Aguiar; Leitão, Terezinha do Menino Jesus Silva (Journal of Health & Biological Sciences, 2021)
Objective: To investigate the mortality attributed to fungal infections, in Brazil between 2003 and 2013. Methods: This ecological study relied on official data collected from the Sistema de Informação Sobre Mortalidade – Mortality Information System database. The mycoses were identified by the 10th revision of the International Classification of Diseases, which included categories B35–B49 in its first chapter. Results: Overall, 11,991,935 deaths were reported in the aforementioned period. The deaths of 4,192 individuals were primarily attributed to mycoses. High annual mortality rates were observed in all Brazilian regions, except in the Northeast. The main recorded mycoses were paracoccidioidomycosis (35.6%) and cryptococcosis (24.1%). There was a downward trend in the number of deaths due to paracoccidioidomycosis. In addition, 10,925 death certificates listed mycoses as an associated cause of death. Cryptococcosis (89.7%) and histoplasmosis (89.4%) were the most common mycoses associated with deaths in HIV patients. Conclusions: There was a downward trend in the number of deaths stemming from invasive fungal infections. However, opportunistic mycoses follow been a significant cause of death, especially in HIV patients.